2020
DOI: 10.1002/jsfa.10580
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different types of mulch on soil properties and tea production and quality

Abstract: BACKGROUND: Tea is an important economic crop in China. Mulching, a modern agricultural practice, can modify the soil microenvironment and maintain the crop yield. RESULTS: To investigate the effect of different mulching modes on tea plant growth, filed experiments were conducted in a Shizipu tea plantation located in Langxi Country (Xuanchen City, Anhui Province, China). Five treatments were carried out in a randomized complete block arrangement: (i) clean tillage (control); (ii) black plastic film; (iii) wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…This discrepancy can be attributed to the speci c soil texture requirements of tea trees. Tea trees typically thrive in loose and well-aerated soil [17] , which facilitates root development and extension, enhancing the absorption of oxygen and nutrients. Conversely, overly sticky soil can impede root respiration, leading to root anoxia and adversely affecting tea tree growth.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy can be attributed to the speci c soil texture requirements of tea trees. Tea trees typically thrive in loose and well-aerated soil [17] , which facilitates root development and extension, enhancing the absorption of oxygen and nutrients. Conversely, overly sticky soil can impede root respiration, leading to root anoxia and adversely affecting tea tree growth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, organic fertilizers and organic mulches that have been applied in the plantations such as fern ( Gleichenia linearis ), Acacia and Eucalyptus barks, rice straw and other plant residues supplemented a high input of organic materials into the tea soils, which can also increase tea soil organic carbon storage and organic matter (Cu & Thu, 2014; Li et al, 2014; Viet San et al, 2021). Tea plants prefer acidic soil with optimal soil pH values from 4.5 to 5.5, but strongly acidic soils could lead to numerous consequences for tea growth and quality, such as nutrient leaching and imbalance, and heavy metal toxicity (Ni et al, 2018; Zhang, Huiguang, et al, 2020; Zhang, Yang, et al, 2020). With regards to soil available P, our results are constrasted with the study by Han et al (2013) who indicated that available P concentrations were significantly different between organically and conventionally managed tea farms.…”
Section: Discussionmentioning
confidence: 99%
“…Agroecological practices aim at optimizing agroecological processes, environmental and public health whilst minimizing social‐ecological costs from agricultural activities (FAO, 2020; Kerr et al, 2021). For tea farming, numerous studies outside Vietnam have indicated the positive impacts of agroecological practices on soil health properties and tea quality indicators, such as the application of organic fertilizers (Gu et al, 2019; Han et al, 2021; Lin et al, 2019) and organic mulching (Zhang, Huiguang, et al, 2020; Zhang, Yang, et al, 2020). Similar positive outcomes have also been recorded from other agroecological practices such as intercropping (Wen et al, 2019; Zhang et al, 2017), agroforestry (Tian et al, 2013) and integrated pest/disease management (Mamun & Ahmed, 2011; Shrestha & Thapa, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the use of high organic amendments such as mulch from pruned residues could explain the low erodibility observed under some tea plantations. The use of mulch protects the soil against the impact of raindrops in addition to increasing soil organic matter, which stabilises the soil aggregates, making them less prone to erosion (Ni et al 2016;Xianchen et al 2020).…”
Section: Spatial Soil Erodibility Mapmentioning
confidence: 99%